Analysis of Factors Affecting Customer Satisfaction in Bread SMEs in Jakarta Using SERVQUAL (Service Quality) Method) - Wilujeng, Fuji Rahayu; Herlina, Herlina (Formosa Journal of Applied Sciences, 2025)
Industry in the food and beverage sector in Indonesia plays an important role in sustaining the development of manufacturing and the national economy, continues to progress. One of the industries engaged in the food and beverage sector is the bread industry. Bread is a processed food whose demand pattern has also increased. This is due to the development of the middle class population, the increase in the income of young people, and the consumption patterns of people who are increasingly shifting to practical urban consumption patterns. SMEs are a business sector that has a significant impact on improving the economy in developing countries. The results of this study are expected to support the performance of SME Bread business actors in general and SME culinary business actors in particular by improving and maintaining variables that greatly affect the quality of these services so that consumers remain loyal to make purchases.